EVALUATION OF INFORMATION SECURITY USING THE INFORMATION SECURITY METHOD (KAMI) Case Study: UPT TIK UNIVERSITY MUHAMMADIYAH BENGKULU - Khairullah, Khairullah; Alam, RG Guntur; Mahfuzi, AR. Walad; Abdullah, Dedy; Fransiska, Nora (Institut Bakti Nusantara, 2025)
In the rapidly evolving digital era, educational institutions increasingly rely on information technology to manage data. However, information security is a critical issue because institutional data is an asset that is vulnerable to threats. This research aims to analyse how the OUR Index Method works in evaluating and measuring the level of information security at UPTIK. The methods used in this research include literature study to understand the concept of information security, primary data collection through interviews and questionnaires, and secondary data from policy documents and audit reports. Data analysis was conducted to compare the condition of information security at UPTIK with the standards set by OUR Index, which is based on SNI ISO/IEC 27001. The expected result of this research is a deeper understanding of the maturity level of information security at UPTIK, as well as the identification of weaknesses and potential risks. With this evaluation, it is expected that institutions can improve their information security posture, prepare for threats, and ensure that the security system implemented is in accordance with applicable standards. This research is expected to make a significant contribution to the management of information security in the educational environment, as well as a reference for other institutions that want to conduct similar evaluations.